Quality of English - Indonesian Translation of English Department Students and Non – English Department Students of Universitas Negeri Semarang - Titus Adhi Sukmana; Rudi Hartono; Hendi Pratama (International Conference on Science, Education, and Technology, 2022)
Abstract. This research aimed to describe the students’ translation quality in translating English into Indonesian text. The researcher used simple random sampling and selected some students to be participants of this research. In this research, the researcher collected the data using document analysis and questionnaire. The data were taken purposively from English Department students and Non – English Department students of Universitas Negeri Semarang (UNNES). After collecting the data, the researcher used rubric to find out the translation quality and questionnaire to find out the factors that affected students’ translation quality. To analyze the quality of students’ translation the researcher using three aspects of translation quality assessment namely, accuracy, clarity and naturalness (Larson,1998). The result of this research showed that the quality of both two groups of students’ translation in translating texts from English into Bahasa Indonesia was good in accuracy aspect. But based on the aspect of clarity, the English Department students gathered relatively better result than the Non – English Department Students. On the aspect of naturalness, the Non – English Department students gathered relatively better result than English Department students. Based on the results of this research, the researcher found that some factors affected the quality of the students’ translation in translating the texts with some challenges that they faced such as some words are difficult to understand, hard to find their equivalent Indonesian words, one word possess many different meanings, ambiguity, cultural aspect, etc.